2017
DOI: 10.1038/nplants.2017.33
|View full text |Cite
|
Sign up to set email alerts
|

Two mechanisms for dissipation of excess light in monomeric and trimeric light-harvesting complexes

Abstract: Oxygenic photoautotrophs require mechanisms for rapidly matching the level of chlorophyll excited states from light harvesting with the rate of electron transport from water to carbon dioxide. These photoprotective reactions prevent formation of reactive excited states and photoinhibition. The fastest response to excess illumination is the so-called non-photochemical quenching which, in higher plants, requires the luminal pH sensor PsbS and other yet unidentified components of the photosystem II antenna. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
114
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 59 publications
10
114
0
Order By: Relevance
“…The stronger difference observed when comparing C. reinhardtii and A. thaliana mutants depleted of monomeric CP26 and CP29 subunits is the NPQ phenotype. In an A. thaliana mutant without monomeric antennae, NPQ activation was slower in dark‐to‐light transition, but after a few minutes of illumination, the quenching was identical to Wt (Dall'Osto et al, ; Townsend et al, ). In the case of C. reinhardtii , in the absence of CP29, an almost halved NPQ phenotype was detected, whereas the double‐mutant k69 presented a no‐NPQ phenotype even after 30 min of illumination at high light intensity (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stronger difference observed when comparing C. reinhardtii and A. thaliana mutants depleted of monomeric CP26 and CP29 subunits is the NPQ phenotype. In an A. thaliana mutant without monomeric antennae, NPQ activation was slower in dark‐to‐light transition, but after a few minutes of illumination, the quenching was identical to Wt (Dall'Osto et al, ; Townsend et al, ). In the case of C. reinhardtii , in the absence of CP29, an almost halved NPQ phenotype was detected, whereas the double‐mutant k69 presented a no‐NPQ phenotype even after 30 min of illumination at high light intensity (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The specific role of CP26 and CP29 in state transitions and NPQ induction herein described reveals a strong difference in the function of monomeric antenna proteins among A. thaliana and C. reinhardtii . In plant, monomeric antenna are not essential for NPQ, and their absence does not abolish state transitions (Dall'Osto et al, ; Townsend et al, ), whereas in the latter, both adaptive mechanisms require the presence of CP26 and/or CP29.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Dall'Osto and coworkers concluded that the trimeric light-harvesting complex II (LHCII) is the location of a more slowly activated (several minutes) quenching mechanism that does not involve formation of Zea •+ in vivo. 13 This implies that CT quenching may be one of multiple quenching (qE) mechanisms.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…Two different enzymes are capable of synthesizing Z: (1) β‐carotene hydroxylase, which synthesizes Z from β‐carotene in a non‐reversible reaction (Tian et al ) and (2) violaxanthin de‐epoxidase (VDE), which catalyzes the de‐epoxidation of violaxanthin (V) to antheraxanthin (A) and then to Z (Saga et al ). This two‐step reaction has been traditionally considered to be light‐dependent and can be reverted by a third enzyme: zeaxanthin epoxidase (ZE), which epoxidates Z back to V, closing the so‐called xanthophyll or V‐cycle (Müller et al , Ruban et al , Demmig‐Adams et al , Jahns and Holzwarth , Dall'Osto et al ). The conversion of V to Z is associated with conformational changes in the antennae and with enhanced dissipation of energy as heat (NPQ), that overall have a vital photoprotective role in the photosynthetic apparatus (Demmig‐Adams , Johnson et al , Leuenberger et al ).…”
Section: Introductionmentioning
confidence: 99%